Verso un'estetica umida. Attraversamenti artistici alla foce del fiume Oreto (Itinera, 2025)
Towards a wet aesthetic. Artistic crossings at the mouth of the Oreto RiverThis essay explores the concept of wet aesthetics as a situated form of aesthetic and political experience that emerges from the interplay between art, ecology, and environmental technologies. Through an analysis of the U-DATInos project, created by the artists Salvatore Iaconesi and Oriana Persico for the Ecomuseo Mare Memoria Viva in Palermo, the text investigates how water –  in its material and symbolic configurations – can become an epistemological and affective medium capable of activating post-anthropocentric forms of sensitivity. Drawing on the methodological tools of the Blue Humanities, wet ontologies, and the thought of scholars such as Astrida Neimanis, Karen Barad, and Donna Haraway, the essay proposes a reading of the artistic practice at the mouth of the Oreto River as a device for activating a wet aesthetics that enables sensory reconfiguration, multispecies intra-action, and ecological citizenship. U-DATInos, through the participatory use of environmental data, shapes an immersive experience that reconnects human and more-than-human bodies to the river, fostering a relational form of custodianship that challenges the boundaries between nature and culture, between data and affect. Wet aesthetics, as outlined here, emerges as a sensitive and transformative practice that translates the porosity of the living into embodied experience, opening up new forms of alliance among water, technology, and community.
Keywords: wet aesthetics; hydrocommons; artistic practices; datapoiesis